Photobiochemical changes in Chlorella g120 culture during trophic conversion (metabolic pathway shift) from heterotrophic to phototrophic growth regime - Babaei, Azadeh (2020)
Physiological and photobiochemical changes and growth in the heterotrophic strain Chlorella vulgaris g120 were studied during trophic conversion from heterotrophic to phototrophic growth regime. After the exposure of the Chlorella g120 culture to light, it revealed a significant activity of the electron transport (450–700 μmol e− m−2 s −1 as measured by chlorophyll fluorescence) and high PSII photochemical yield Fv/Fm between 0.7 and 0.8. Fast fluorescence induction kinetics showed that PSII electron acceptors in the plastoquinone pool remained partly oxidized, indicating no downregulation of PSII electron transport. The data further revealed that high photobiochemical activity is lost in futile (protective) processes of non-photochemical quenching and respiration which indicate that surplus energy is dissipated in these processes. Pigment analysis showed low chlorophyll content − 0.35–1.15% as compared with exclusively phototrophic strain Chlorella vulgaris R-117. Nevertheless, the carotenoid content in g120 was relatively high − 0.20–0.33% of dry weight which resulted in a considerably high ratio of carotenoid/chlorophyll − 0.31–0.44. This strain probably does not possess the fully competent photosynthetic apparatus and can only partially adapt to phototrophy. We show that the heterotrophically grown g120 strain can undergo metabolic shift from heterotrophic to phototrophic growth regime. It might be an interesting strain from biotechnological point of view as a source of carotenoids, especially lutein.